2022
DOI: 10.1016/j.iccn.2021.103123
|View full text |Cite
|
Sign up to set email alerts
|

The impact of family visitor restrictions on healthcare workers in the ICU during the COVID-19 pandemic

Abstract: Purpose To obtain information on how family visitor restriction during the COVID-19 pandemic has impacted the workplace experience of physicians and nurses in the medical intensive care unit, and to assess differences by profession. Materials and methods We developed a survey containing closed- and open-ended questions, applying both quantitative and qualitative analyses to our results. Results Of the 74 respondents, 29 (38%) were nurses and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 45 publications
5
30
0
Order By: Relevance
“…Some elimination strategies, notably visitor restrictions, have been associated with negative impacts on patient, HCP, and family well-being in terms of social isolation, reduced quality of life, emotional distress, and difficulty with end-of-life care, and have been reconsidered since the initial phase of the pandemic. 21 , 22 Prior to the COVID-19 pandemic, studies showed that allowance of visitors did not increase risk of infection but did reduce frequency of delirium and anxiety-related symptoms in patients and family satisfaction. 23 The postponement of routine or emergency medical care has led to delayed diagnoses of malignancies and avoidable and ongoing excess morbidity and mortality.…”
Section: Eliminationmentioning
confidence: 99%
“…Some elimination strategies, notably visitor restrictions, have been associated with negative impacts on patient, HCP, and family well-being in terms of social isolation, reduced quality of life, emotional distress, and difficulty with end-of-life care, and have been reconsidered since the initial phase of the pandemic. 21 , 22 Prior to the COVID-19 pandemic, studies showed that allowance of visitors did not increase risk of infection but did reduce frequency of delirium and anxiety-related symptoms in patients and family satisfaction. 23 The postponement of routine or emergency medical care has led to delayed diagnoses of malignancies and avoidable and ongoing excess morbidity and mortality.…”
Section: Eliminationmentioning
confidence: 99%
“…Evidence also suggests that visitor restriction policies related to COVID-19 delayed important goals of care decisions and may have prolonged the suffering of patients in the ICU who ultimately died ( 8 ). The absence of family at the bedside may have complex effects on the experiences of ICU clinicians ( 9 ). However, difficulties with communication, loss of the humanizing presence of families, and witnessing patient deaths without family present may increase the burnout and moral distress that is now endemic among those caring for patients in the ICU during the COVID-19 pandemic ( 9 , 10 ).…”
mentioning
confidence: 99%
“…The absence of family at the bedside may have complex effects on the experiences of ICU clinicians ( 9 ). However, difficulties with communication, loss of the humanizing presence of families, and witnessing patient deaths without family present may increase the burnout and moral distress that is now endemic among those caring for patients in the ICU during the COVID-19 pandemic ( 9 , 10 ).…”
mentioning
confidence: 99%
“…Whilst the rationale as an infection prevention and control measure may be mostly understood, keeping families away from dying patients opposes cultural norms and prevents families from fulfilling their desired caring role, and contributes to family suffering and distress at the end of life ( Bloomer & Walshe, 2021 ). A survey designed to explore how family visitor restrictions during the COVID-19 pandemic impacted ICU clinicians in the USA identified that whilst clinicians spent more time using telephone and web-based applications to facilitate communication and a connection between patients, families and clinicians, clinicians also reported negative impacts on end-of-life care, associated with decreased comprehension and greater emotional distress for family members ( Wendlandt et al, 2022 ). Whilst facilitating family presence at the bedside must remain a priority, at the very least, the lessons learnt during COVID-19 demonstrate how the value of virtual visiting should not be overlooked in situations where families may be unable to visit due to distance, time or other factors.…”
mentioning
confidence: 99%
“…Yet cultural differences can potentiate confusion and conflict ( Brooks et al, 2019 ), likely amplified when visitor restrictions are in place. Family visitor restrictions were also challenging for nurses, bearing the responsibility of holding the dying person’s hand in place of a family member ( Wendlandt et al, 2022 ). A Norwegian study exploring critical care nurses’ experiences of withdrawal of life-sustaining treatments highlighted that disagreements in decision-making, concerns about overtreatment and prolonging patient suffering were a source of distress for nurses ( Taylor et al, 2020 ).…”
mentioning
confidence: 99%